Conditional value-at-risk optimization for managing area pricing risk in the Finnish electricity market - Kramb, Jason (2021)
Differences in area pricing in the Nordic electricity markets creates price risk for large electricity consuming industries. The thesis will present a method to determine the optimal amount of electricity price area differentials (EPAD) futures to purchase for hedging area price risk in the Finnish electricity market for a large electricity consumer. A hedging portfolio was constructed by minimizing total electricity costs subject to the constraint that the conditional value at risk (CVaR) stays below a given level. To illustrate how this method can be used in practice, three simple forecasting models were developed to predict the futures premium for the Finnish area price. These forecasting models are used to generate possible future scenarios of the future premium, which is then used in the hedging portfolio optimization to minimize CVaR. The performance of the CVaR hedging strategies using different forecasting methods is compared against the performance of minimum variance and two fixed hedge ratio strategies.